Multidimensional Tourism Development Strategy as a Driver of the Creative Economy: A Study of the Pahlawan Street Center Area in Madiun City - Malik Ibrahim; Nuril Endi Rahman; Fajar Istikhomah; Siti Komala Mutiara (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to (1) explore multidimensional tourism development strategies in the Pahlawan Street Center Area as a driver of the creative economy. (2) Examine the role of stakeholders in designing multidimensional tourism development strategies that have an impact on the creative economy. (3) Analyze the potential of multidimensional tourism in Pahlawan Street Center in supporting the development of the creative economy. (4) Social learning and cultural awareness in multidimensional tourism development. (5) Community empowerment and creative economy education. (6) Integration of multidimensional tourism and local policies as a pedagogical model. Methodology: This research uses descriptive qualitative research, data collection using non-participant observation, semi-structured interviews with 12 informants, and documentation. Data analysis uses reduction, data presentation, and conclusion drawing, while data validity uses source and method triangulation. Main Findings: The multidimensional tourism development strategy in Pahlawan Street Center is carried out through the organization of events, the formation of the Creative Economy Committee, Kawista, Dekranasda, and MSME Stands with synergy between stakeholders as planners and executors. This tourism potential supports the creative economy, cultural preservation, the formation of city identity, and multicultural education. In addition, community empowerment and creative economy education encourage independence, entrepreneurship, economic equality, and create a sustainable development model based on local policies and socio-cultural resilience. Novelty/Originality of this study: This study explores multidimensional tourism as a driver of the creative economy. The role of stakeholders and the potential of creative economy products. Social learning and cultural awareness. Community empowerment and creative economy education. The integration of multidimensional tourism and local policies as a pedagogical model.